Thin Capitalization, Tax Haven Utilization, and Political Connections: Their Collective Impact on Corporate Tax Aggressiveness - Yuliasari, Rahmahilah; Rifan, Dinda Fali; Selvina, Mia (E-Jurnal Akuntansi; Vol 35 No 1 (2025)DO - 10.24843/EJA.2025.v35.i01.p17, 2025)
This study examines the impact of thin capitalization, tax haven utilization, and political connections on corporate tax aggressiveness. The research focuses on manufacturing firms within the consumer goods sector listed on the Indonesian Sharia Stock Index (ISSI) from 2019 to 2023. The study employs a quantitative approach using secondary data. A non-probability sampling method, specifically purposive sampling, is applied, resulting in a final sample of 12 companies with a total of 60 firm-year observations. To analyze the data, multiple linear regression is conducted using SPSS software. The findings indicate that thin capitalization and tax haven utilization do not significantly influence tax aggressiveness. However, political connections exhibit a positive and significant relationship with tax aggressiveness, suggesting that politically connected firms are more likely to engage in aggressive tax planning strategies. Keywords: Thin Capitalization; Tax Haven Country Utilization; Political Connection; Tax Aggressiveness